ANALISIS TINGKAT LITERASI KEUANGAN DALAM PENGELOLAAN DANA BOS DI SMP NEGERI 40 PEKANBARU - Ainil Huda; Gusnardi Gusnardi; RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This study aims to analyze the level of financial literacy and the level of financial management of financial managers in particular the management of School Operational Cost funds at Junior High Schools 40Pekanbaru, The data in the study of primary data in the form of questionnaires and secondary data sourced from financial statement data Operational Cost funds Junior High School 40 Pekanbaru.. Sampling with saturated sampling technique where all populations are sampled. The data analysis technique used is quantitative descriptive analysis by using SPSS (Statistical Package for Social Science) program. The results showed that the level of financial literacy of Operational Cost funds managers in Junior High School 40 Pekanbaru was classified as high because it was in the Suff Literate category, the level of management of Operational Cost funds in Junior High School 40 Pekanbaru was also in the very high category. the Operational Cost funds supervision indicator is the indicator that dominates the highest value of the 3 (three) other indicators with an average value reaching 10. This proves that the supervision of Operational Cost funds in Junior High School 40 Pekanbaru has been done very well.Key Words: Financial Literacy, Financial Management